2020
DOI: 10.7759/cureus.9161
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence in Older Adults Takes Collaborative Nursing Efforts to Improve

Abstract: There is a misconception that urinary incontinence (UI) in older adults, usually above the age of 65 is a part of aging. More than 50% of residents in long-term care (LTC) settings are affected by UI and it is associated in many cases with markedly reduced quality of life. It has become evident that incontinence can be cured or successfully managed. However, many nurses lack sufficient knowledge to intervene appropriately. The purpose of this review is to share how the collaborative efforts of nurses at all le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…The use of bladder scanners in LTC focuses on the needs and services for the older and often frail populations. Older adults are at higher risk for bladder dysfunction and because continence care is an important quality of life indicator for people living in LTC, it is essential for health care providers to accurately assess residents for bladder problems (Caliskan et al, 2019; Dingwall, 2008; McDaniel et al, 2020; Newman et al, 2005). The responses from participants in this study highlight their understanding of the benefit of using the bladder scanners, yet the uptake of their use is still limited in the nursing care staff’s routine practice and management of continence issues.…”
Section: Discussionmentioning
confidence: 99%
“…The use of bladder scanners in LTC focuses on the needs and services for the older and often frail populations. Older adults are at higher risk for bladder dysfunction and because continence care is an important quality of life indicator for people living in LTC, it is essential for health care providers to accurately assess residents for bladder problems (Caliskan et al, 2019; Dingwall, 2008; McDaniel et al, 2020; Newman et al, 2005). The responses from participants in this study highlight their understanding of the benefit of using the bladder scanners, yet the uptake of their use is still limited in the nursing care staff’s routine practice and management of continence issues.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of life is impaired in urinary incontinence and with the limitation of physical activity. Furthermore; the incidences of hypertension, osteoporosis, coronary heart disease, and psycho-social problems increase in this age group (23).…”
Section: Genitourinary Systemmentioning
confidence: 99%
“…Treatment patterns related to OAB within the nursing home setting are also not fully characterized, which is of particular concern given the overall health of these individuals as well as the potential for adverse events associated with polypharmacy [6]. Although comprehensive treatment guidelines exist, current literature indicates that the management of OAB/UI in the nursing home setting is challenging [7,8]. Behavioral interventions are recommended as first-line treatment; however, multiple studies have found that nursing home staff do not have the adequate training or knowledge to manage OAB/UI using these techniques [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although comprehensive treatment guidelines exist, current literature indicates that the management of OAB/UI in the nursing home setting is challenging [7,8]. Behavioral interventions are recommended as first-line treatment; however, multiple studies have found that nursing home staff do not have the adequate training or knowledge to manage OAB/UI using these techniques [8][9][10]. Following behavioral therapies, the first line of pharmacotherapy in OAB patients typically consists of antimuscarinic agents, which are part of the group of oral anticholinergic medications [11].…”
Section: Introductionmentioning
confidence: 99%